Redundant microtubule crosslinkers prevent meiotic spindle bending to ensure diploid offspring in C. elegans. - Wenzhe Li; Helena A Crellin; Dhanya Cheerambathur; Francis J McNally (PLoS Genetics, 2023)
Oocyte meiotic spindles mediate the expulsion of ¾ of the genome into polar bodies to generate diploid zygotes in nearly all animal species. Failures in this process result in aneuploid or polyploid offspring that are typically inviable. Accurate meiotic chromosome segregation and polar body extrusion require the spindle to elongate while maintaining its structural integrity. Previous studies have implicated three hypothetical activities during this process, including microtubule crosslinking, microtubule sliding and microtubule polymerization. However, how these activities regulate spindle rigidity and elongation as well as the exact proteins involved in the activities remain unclear. We discovered that C. elegans meiotic anaphase spindle integrity is maintained through redundant microtubule crosslinking activities of the Kinesin-5 family motor BMK-1, the microtubule bundling protein SPD-1/PRC1, and the Kinesin-4 family motor, KLP-19. Using time-lapse imaging, we found that single depletion of KLP-19KIF4A, SPD-1PRC1 or BMK-1Eg5 had minimal effects on anaphase B spindle elongation velocity. In contrast, double depletion of SPD-1PRC1 and BMK-1Eg5 or double depletion of KLP-19KIF4A and BMK-1Eg5 resulted in spindles that elongated faster, bent in a myosin-dependent manner, and had a high rate of polar body extrusion errors. Bending spindles frequently extruded both sets of segregating chromosomes into two separate polar bodies. Normal anaphase B velocity was observed after double depletion of KLP-19KIF4A and SPD-1PRC1. These results suggest that KLP-19KIF4A and SPD-1PRC1 act in different pathways, each redundant with a separate BMK-1Eg5 pathway in regulating meiotic spindle elongation. Depletion of ZYG-8, a doublecortin-related microtubule binding protein, led to slower anaphase B spindle elongation. We found that ZYG-8DCLK1 acts by excluding SPD-1PRC1 from the spindle. Thus, three mechanistically distinct microtubule regulation modules, two based on crosslinking, and one based on exclusion of crosslinkers, power the mechanism that drives spindle elongation and structural integrity during anaphase B of C.elegans female meiosis.